CO2 reforming of methane to syngas over highly active and stable supported CoOx (accompanied with MgO, ZrO2 or CeO2) catalysts - Mondal, Kartick C.; Choudhary, Vasant R.; Joshi, Upendra A. (Applied Catalysis A-General, 2007)
{Catalytically inactive CoOx-MgO (calcined at 900 degrees C) becomes highly active and selective in the CO2 reforming of methane to syngas when it is deposited on a commercial low surface-area macro-porous silica-alumina support (SA-5205) or when CoOx is deposited on the support precoated with MgO. Both the supported CoOx and MgO containing catalysts (CoOx -MgO/SA-5205 and CoOx/MgO/SA-5205) show high methane conversion (> 98%) activity and H-2 selectivity (> 94%) and also high stability against carbon deposition [
Keywords: arylboronic acids; diarylmethylidenefluorene; dibromomethylidenefluorene; Pd-mediated coupling; Suzuki reaction

Palladium impregnated amine Co-condensed hexagonal mesoporous silica: a novel catalyst in tailoring suzuki and heck coupling reactions in base free condition - Das, Prangya Paramita; Prabhakaran, Vinod C.; Nanda, Samik; Sen, Debasis; Chowdhury, Biswajit (ChemistrySelect, 2019)
Palladium impregnated amine co-condensed hexagonal mesoporous silicas (HMS-X) were synthesized (sol-gel process) using different amines (Ethylene diamine and pyridine) of various concentrations (0.25 equiv. and 2 equiv.). The effect of amine concentration on the local structure of hexagonal mesoporous silica was studied. The catalyst shows excellent catalytic activity and high TOF towards both Suzuki and Heck coupling reactions without using any base in reaction medium with the solvent DMF:water in (1:1) ratio. The catalyst was reused and it was recyclable up to three cycle without any appreciable loss of activity and the kinetics of the reaction varying different parameters also have been studied thoroughly.
Keywords: Amine functionalized silica; Base free; Heck reaction; Palladium supported catalysts; Suzuki reaction